New report on anatomy of lenticel development in Fraxinus (Oleaceae) species from Iran - Kaveh, Mona; Tavassoli, Akhtar; Memariani, Farshid; Azadi, Rahman (Acta Biologica Szegediensis, 2015)
The adaptive abilities of plants allow them to survive in wide ranges of physical conditions. These adaptations appeared to be associated with lenticels. Lenticels are essential to the plants, since they control gas exchange in the absence or losing the function of stomas. Fraxinus is a morphologically variable genus and this is regarded as individual adaptations to environmental conditions. Plant adaptations to different environmental conditions can also influence their anatomical structures. In present study, the anatomical features of leaf petioles and fruits were examined in two Fraxinus species from Iran. Samples of young to mature petiole and fruit samples were collected from the trees. The anatomical observations revealed different origins of lenticel development which are recorded for the first time. Lenticels on the petioles have epidermal origin however lenticels on the fruits are originated from stomas.